Risk factors of stoma re-creation after closure of diverting ileostomy in patients with rectal cancer who underwent low anterior resection or intersphincteric resection with loop ileostomy - Song, Ook (Ann Surg Treat Res, 2018)
PURPOSE: The aim of this study was to identify the risk factors of stoma re-creation after closure of diverting ileostomy in patients with rectal cancer who underwent low anterior resection (LAR) or intersphincteric resection (ISR) with loop ileostomy. METHODS: We retrospectively reviewed 520 consecutive patients with rectal cancer who underwent LAR or ISR with loop ileostomy from January 2005 to December 2014 at Chonnam National University Hwasun Hospital. Risk factors for stoma re-creation after ileostomy closure were evaluated. RESULTS: Among 520 patients with rectal cancer who underwent LAR or ISR with loop ileostomy, 458 patients underwent stoma closure. Among these patients, 45 (9.8%) underwent stoma re-creation. The median period between primary surgery and stoma closure was 5.5 months (range, 0.5–78.3 months), and the median period between closure and re-creation was 6.8 months (range, 0–71.5 months). Stoma re-creation was performed because of anastomosis-related complications (26, 57.8%), local recurrence (15, 33.3%), and anal sphincter dysfunction (3, 6.7%). Multivariate analysis showed that independent risk factors for stoma re-creation were anastomotic leakage (odds ratio [OR], 4.258; 95% confidence interval [CI], 1.814–9.993), postoperative radiotherapy (OR, 3.947; 95% CI, 1.624–9.594), and ISR (OR, 3.293; 95% CI, 1.462–7.417). CONCLUSION: Anastomotic leakage, postoperative radiotherapy, and ISR were independent risk factors for stoma re-creation after closure of ileostomy in patients with rectal cancer.